1999
DOI: 10.5194/aab-42-601-1999
|View full text |Cite
|
Sign up to set email alerts
|

Inzuchtdepression bei Merkmalen der Fruchtbarkeit und der Gewichtsentwicklung beim Göttinger Miniaturschwein

Abstract: SummaryTitle of the paper: Inbreeding depression for litter traits and the development of growth in the Göttinger Minipig A data set of 1191 litters from 282 sows and 6777 piglets weights from the Göttinger Minipig was analysed to estimate inbreeding depression for litter traits and the early growth rates up to an age of 12 month. The population ofthe Göttinger Minipig shows an average inbreeding of sows and piglets of about 10 % with a Standard deviation of 1.7 % with a nearly normal distribution of the inbre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Other ϳ6-to 12-mo-old male Göttingen minipigs were used for the reproducibility study. Characteristics of this pig strain have been described in detail previously (10,15). The pigs were allowed an acclimatization period of 3 wk during which they were gradually introduced to their diets and trained in the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other ϳ6-to 12-mo-old male Göttingen minipigs were used for the reproducibility study. Characteristics of this pig strain have been described in detail previously (10,15). The pigs were allowed an acclimatization period of 3 wk during which they were gradually introduced to their diets and trained in the experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…An intravenous glucose bolus of 0.3 g/kg (glucose, 500 g/l; SAD) was administered in 25 pigs over 30 s after collection of basal samples at Ϫ20, Ϫ10, Ϫ3, Ϫ2, and 0 min. Blood samples were then collected at 1, 2, 3, 4, 5,6,7,8,10,12,14,16,18,20,30,45,60,90, and 120 min. In the reproducibility experiment blood samples were taken at Ϫ10, Ϫ5, 0, 2,5,10,15,20,25,30,40,50,60,70,80,90, 100, 110, and 120 min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore animals with an inbreeding coefficient between 6.0 to 12.5 % showed an extended test time of 6.5 days. BRANDT and MÖLLERS (1999) in Göttinger Minipig population found that a 10 % increase of inbreeding of sows or litters both leads to a reduction on weight within the first 6 months of 0.25 kg. According to CURIK et al (2001) the inbreeding depression is determined by:…”
Section: Genetic Parameters Estimationmentioning
confidence: 99%
“…One can consider that the leg axis might also differ between immature and adult individuals. The limited genetic pool in the closed pig population used for breeding the Go¨ttingen minipig 15 could also influence it. However, no lameness or cartilage degeneration could be observed in adult Go¨ttingen minipigs used for orthopaedic studies (own non-published results).…”
Section: Discussionmentioning
confidence: 99%
“…These miniature pigs have an inbreeding coefficient below 10%. 15 Ko¨hn et al 16 could show differences in the growth development of both pig lines; the hybrid pig shows the classical sigmoid growth pattern, whereas the Go¨ttingen minipig revealed an almost linear growth curve. 13 So, the question arises whether these both pig lines might show differences in joint macroanatomy and cartilage histology, or whether divergent articular chondrocyte biology is detectable which might influence the outcome of orthopaedic cartilage repair studies.…”
Section: Introductionmentioning
confidence: 96%